Inter-Disciplinary Conservative Management of Bilateral Non-United Lumbar Pars Defects in a Junior Elite Golfer - Simon L Brearley; Orlaith Buckley; Patrick Gillham; Bryan Clements; Daniel Coughlan (International Journal of Sports Physical Therapy)
The prevalence of spondylolysis amongst adolescent athletes presenting with low back pain has been reported as high as 47-55%. Youth athletes participating in sports involving movements combining compression, extension and rotation appear most susceptible. As such, young golfers are a high-risk group, particularly given the high shear and compressive forces associated with the golf swing action. This is compounded by a culture which encourages very high practice volumes, typically poorly monitored. Although non-operative interventions are deemed the gold-standard management for this condition, surgery is indicated for more severe presentations and cases of ‘failed’ conservative management. The case presented herein outlines an inter-disciplinary, non-operative management of a 17-year old elite golfer with a moderate to severe presentation. A 4-stage model of reconditioning is outlined, which may be of use to practitioners given the paucity of rehabilitation guidelines for this condition. The report highlights the benefits of a graded program of exercise-based rehabilitation over the typically prescribed “12 weeks rest” prior to a return to the provocative activity. It also supports existing evidence that passive therapeutic approaches should only be used as an adjunct to exercise, if at all in the management of spondylolysis. Finally, and crucially, it also underlines that to deem non-surgical rehabilitation ‘unsuccessful’ or ‘failed’, clinicians should ensure that (long-term) exercise was included in the conservative approach.